2005
DOI: 10.1007/s10926-005-8038-8
|View full text |Cite
|
Sign up to set email alerts
|

Workplace-Based Return-to-Work Interventions: A Systematic Review of the Quantitative Literature

Abstract: Our systematic review provides the evidence base supporting that workplace-based RTW interventions can reduce work disability duration and associated costs, however the evidence regarding their impact on quality-of-life outcomes was much weaker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
422
0
15

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 603 publications
(459 citation statements)
references
References 53 publications
22
422
0
15
Order By: Relevance
“…High mobility may also impoverish the organization as competence and human capital investment disappear with employees who quit [52]. The results thus give support to the common finding that employer engagement involving support and work place adjustments for sick-listed workers may facilitate health and work ability [2,4,23].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…High mobility may also impoverish the organization as competence and human capital investment disappear with employees who quit [52]. The results thus give support to the common finding that employer engagement involving support and work place adjustments for sick-listed workers may facilitate health and work ability [2,4,23].…”
Section: Discussionsupporting
confidence: 67%
“…A number of studies have shown how interventions at the workplace contribute to return to the original job [1][2][3][4]. These interventions are appropriate for many workers, and contribute to the fact that most people on sick leave resume work within a limited amount of time.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a systematic review completed by Williams et al examined a variety of workplace rehabilitation programs and found that modified work was most effective in facilitating early RTW, reducing disability, reducing pain and decreasing the rate of back injuries [9]. A similar systematic review conducted by Franche et al examined the effects of workplace interventions on early RTW [10]. They found that accommodation and early contact with the worker following injury reduces disability duration [10].…”
Section: Introductionmentioning
confidence: 99%
“…A similar systematic review conducted by Franche et al examined the effects of workplace interventions on early RTW [10]. They found that accommodation and early contact with the worker following injury reduces disability duration [10].…”
Section: Introductionmentioning
confidence: 99%
“…Workplace accommodations are efforts to modify any aspect of a job or work environment to enable people with disabilities to work effectively at their current workplace [9,10]. These are beneficial and effective for both disabled workers and their employers [6,7].…”
Section: Introductionmentioning
confidence: 99%